Analyzing the Product-Market Fit of Kopiah Resam Id - Ahmad Alfisyach, Ryan; Perdhana Dalimunthe, Gallang (Cv. Syntax Corporation Indonesia, 2025)
This research aims to analyze the product-market fit level of Kopiah Resam ID and formulate an appropriate marketing strategy for market development. The research method uses a qualitative approach with in-depth interviews of 15 respondents selected through purposive sampling based on criteria: users with hair-on-fire problems, users who can demonstrate hard facts, and users with future product vision. Data were analyzed using the Sean Ellis Test and Superhuman Framework to measure product-market fit, and the Ansoff Matrix to formulate marketing strategies. The results show that Kopiah Resam ID has achieved product-market fit with a score of 53.3% (above the 40% Sean Ellis Test threshold) and a Product-Market Fit Score of 8.0 out of 10. The recommended marketing strategies are market penetration and market development, focusing on value-based market segmentation (consumers who care about culture and sustainability), positioning as an exclusive premium product, and developing integrated digital and offline distribution channels. This research provides practical contributions for MSMEs in cultural products to achieve business sustainability through a validated product-market fit approach.